Adherence to antiretroviral therapy in people living with HIV with moderate or severe mental disorder - Priscilla Arashiro; Camila Guadeluppe Maciel; Fernanda Paes Reis Freitas; Gabriel Serrano Ramires Koch; João Cesar Pereira da Cunha; Anderson Ravy Stolf; Anamaria Mello Miranda Paniago; Márcio José de Medeiros; Cláudia Du Bocage Santos-Pinto; Everton Falcão de Oliveira (Scientific Reports, 2023)
Abstract Human immunodeficiency virus (HIV) infection remains a serious public health concern, with an estimated 38 million people living with HIV (PLHIV). PLHIV are often affected by mental disorders at higher rate than the general population. One challenge in the control and prevention of new HIV infections is adherence to antiretroviral therapy (ART), with PLHIV with mental disorders having seemingly lower adherence than PLHIV without mental disorders. This cross-sectional study assessed adherence to ART in PLHIV with mental disorders who attended the Psychosocial Care Network health facilities in Campo Grande, Mato Grosso do Sul, Brazil, from January 2014 to December 2018. Data from health and medical databases were used to describe clinical–epidemiological profiles and adherence to ART. To assess the associated factors (potential risk or predisposing factors) with ART adherence, we used logistic regression model. Adherence was extremely low (16.4%). Factors associated with poor adherence were lack of clinical follow-up, particularly in middle-aged PLHIV. Other apparently associated factors were living on the streets and having suicidal ideation. Our findings reinforce the need for improvements in the care for PLHIV with mental disorders, especially in the integration between specialized mental health and infectious disease health facilities.